The absence of fathers and/or mothers and the concept of masculinity and femininity of UPV-CAS students. - Sanapo, Margaret S
The study on the absence of fathers and/or mothers and the concept of masculinity of UPV-CAS students is a descriptive research. It aims to find out whether there are significant differences between males' and females' concept of masculinity and feminity, whether the absence of fathers and/or mothers makes the individuals' concept of masculinity and feminity traditional/nontraditional, whether individuals having both parents employed differ with those having only one parent employed in their concept of masculinity and feminity, and whether individuals' concept on masculinity significantly correlate with their concept of feminity. Findings of the study showed that there are significant differences in the concept of masculinity between individuals in mother-absent and father-absent group and between mother-absent and the rest of the intact family groups except only-mothers-work group. It showed that mother-absent group have a more traditional concept of masculinity than father-absent, only-fathers-work, and both-parents-work group. It also revealed that males significantly differ with females in their concept of masculinity and feminity. It signifies that females have a less traditional concept of masculinity and feminity than do males. Morevoer, all groups except mother-absent showed that there is a significant correlation between their concept on masculinity and their concept on feminity. It implies that when individuals' concept on masculinity is traditional, their concept on feminity is also traditional.